Open reduction and internal fixation of humeral shaft fractures versus conservative treatment with a functional brace: a study protocol of a randomised controlled trial embedded in a cohort - Rämö, Lasse; Taimela, Simo; Lepola, Vesa; Malmivaara, Antti; Lähdeoja, Tuomas; Paavola, Mika (BMJ open, 2017)
IntroductionHumeral shaft fractures represent 1%–3% of all fractures and 20% of humeral fractures in adults. The treatment of these fractures is mainly conservative and operative treatment is usually reserved for specific circumstances. To date, no randomised controlled trial (RCT) has compared operative treatment of humeral shaft fractures with conservative treatment.Methods and analysisWe will conduct an RCT to compare the effectiveness and cost-effectiveness of surgical and conservative treatment of humeral shaft fractures. After providing informed consent, 80 patients from 18 years of age with humeral shaft fracture will be randomly assigned to open reduction and internal fixation with locking plate or conservative treatment with functional bracing. We will follow the patients for 10 years and compare the results at different time points. The primary outcome will be Disabilities of Arm, Shoulder and Hand (DASH) at 12 months. The secondary outcomes will include Numerical Rating Scale for pain at rest and in activities, Constant Score and quality of life instrument 15D. Patients not willing to participate in the RCT will be asked to participate in a prospective cohort follow-up study, ‘the declined cohort’. This cohort will be followed up at the same time points as the randomised patients to assess the potential effect of participation bias on RCT results and to enhance the external validity of the RCT. In one of the recruiting centres, all cooperative patients with humeral shaft fractures not eligible for randomisation will be asked to participate in a ‘non-eligible cohort’ study. We will use blinded data interpretation of the randomised cohort to avoid biased interpretation of outcomes. Our null hypothesis is that there is no clinically relevant difference in the primary outcome measure between the two treatment groups. We will consider a difference of a minimum of 10 points in DASH clinically relevant.Ethics and disseminationThe institutional review board of the Helsinki and Uusimaa Hospital District has approved the protocol. We will disseminate the findings of this study through peer-reviewed publications and conference presentations.Trial registration numberNCT01719887; pre-results.